Intercat aggression – general considerations, prevention and treatment - Moesta, A.; Crowell-Davis, S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2011)
Although cats are a social species and capable of living together in groups of several cats, intercat aggression is a common behavioral problem. Intercat aggression can be classified as status-related, fearrelated, play-related, redirected and can also be due to the addition of a new cat to an existing group. Socialization of kittens, choice of the right cat for a multicat household, and the gradual introduction of a new cat to the household can help to prevent intercat aggression. Treatment of intercat aggression should combine behavior modification, management and – if necessary – medication.
Keywords: Cat; aggression; social behavior; behavior therapy